Comfort Evaluation of the 'Católica' Pedestrian Bridge Based on SETRA 2006 - Lenin Bendezu, R. (2025)
The increasing trend toward slender and low-stiffness pedestrian bridge designs has significantly raised their susceptibility to dynamic excitations induced by pedestrian activity. One of the most critical vibration phenomena in such structures is synchronous excitation, which occurs when the walking frequency of pedestrians coincides with the natural frequency of the bridge. This resonance condition can amplify the structural response, negatively impacting both user comfort and overall structural performance. These challenges are particularly relevant in densely populated urban environments such as Lima. In this study, the dynamic behavior and comfort performance of the “Católica” pedestrian bridge were evaluated through in-situ vibration measurements using a geophone-based seismograph. The recorded data were analyzed based on the SETRA guideline, which classifies comfort into four levels according to peak vertical acceleration. This international reference was selected because, unlike the Peruvian bridge design standards—which do not explicitly consider pedestrian-induced vibrations as a dynamic load—the SETRA guideline has been applied in similar studies within the national context and offers more specific criteria for evaluating pedestrian comfort. The results showed that vertical accelerations reached up to 0.541 g (5.31 m/s2) during pedestrian activity, corresponding to the lowest comfort level defined by the SETRA guideline. While most structural frequencies remained outside the resonance range, certain transverse modes during loading approached 1.2 Hz—a value close to the typical walking frequency range of pedestrians (1.7-2.3 Hz)suggesting a moderate potential for dynamic amplification. Although no clear resonance was detected, the elevated acceleration levels observed under normal use conditions highlight the need to implement vibration mitigation measures. At this stage of the study, no single solution is prescribed. However, there is a recognized need to evaluate and compare various mitigation strategies in order to determine the most appropriate approach. These may include Tuned Mass Dampers (TMDs), damping pads, tuned stiffness elements, or minor structural modifications. A comparative assessment considering technical performance, ease of implementation, and cost-effectiveness would help identify the optimal solution. Such measures would allow the bridge to comply with the SETRA Level 1 comfort threshold (0.5 m/s2), thereby enhancing both safety and user comfort.